Managing difficulties associated with multi-grade classes in Mpumalanga primary schools - Ntombela, Sipho Shadrack (My University, 2021)
The Department of Basic Education has a duty of ensuring that all children enjoy free and equal access to basic education despite their socio-economic status and backgrounds. The South African constitution also recognises universal access to quality primary education as a fundamental human right. This compels the Department of Basic Education to ensure that every child is provided with basic primary education at no cost, hence the expansion of no-fee schools and the National Schools Nutrition Programme. In an attempt to fulfil the Millennium Developmental Goal 2, which advocates for the provision of equal access to primary education, the multi-grade teaching practice was then introduced to ensure the provision of education to children in sparsely-populated and rural communities. However, this type of teaching practice comes with myriad difficulties which teachers face as they manage curriculum delivery. This study, therefore, seeks to examine the various difficulties that teachers face as they have to deal with multi-grade teaching and how they overcome those difficulties. The literature revealed that multi-grade teaching is not limited to the South African situation alone, but a global phenomenon practised in both developing and developed countries. It also emanates from the literature that multi-grade teaching, if used correctly and effectively could yield positive results. The study adopted a qualitative research approach. This study follows a case study design. Following that the study adopted the qualitative research approach, data collection tools linked to the approach were used and included: Interviews, document review and observations. A principal, teacher and parent from three schools managing difficulties associated with multi-grade classes were purposively sampled. The research findings, based on the interviews, document review, observation and the literature reviewed revealed that the insufficient backing from the Department of Basic Education, heavy workload of teachers and general shortage of teaching staff are some of the difficulties that teachers in multi-graded schools have to grapple with. Based on the findings, the researcher concludes that the dearth of intervention from the Department of Basic Education hugely affects the effective curriculum delivery in multi-graded schools. To mitigate the identified difficulties, the researcher recommended that a different post-provisioning norm and funding model for the multi-graded schools be experimented with.
Thesis (M. Ed. (Curriculum Studies)) -- University of Limpopo, 2021
Keywords: Access to basic education; Multi-grade classess; Curriculum delivery; Multigrade teaching; Combination of grades; Basic education -- South Africa -- Mpumalanga; Education, Primary -- South Africa -- Mpumalanga; Education -- Curricula; Teaching -- South Africa -- Mpumalanga